2023
DOI: 10.1186/s44147-023-00196-7
|View full text |Cite
|
Sign up to set email alerts
|

A review—metastable β titanium alloy for biomedical applications

Abstract: Titanium and its alloys have already been widely used as implant materials due to their outstanding mechanical characteristics and biocompatibility. Notwithstanding this, researchers and businesses alike have continued to actively pursue superior alloys since there are still problems which need urgent consideration. One of these is a noteworthy difference in the implant material’s elastics modulus and that of natural bone, which result into an issue of stress shielding. With prolonged use Ti alloys releases da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 210 publications
0
3
0
Order By: Relevance
“…The results of X-ray diffraction measurements for Ti-50Nb-xMo system samples are shown in Figure 6 . It can be observed that the diffractograms presented characteristic peaks of a cubic structure of the centered body, which is typical of the β phase of this alloy [ 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of X-ray diffraction measurements for Ti-50Nb-xMo system samples are shown in Figure 6 . It can be observed that the diffractograms presented characteristic peaks of a cubic structure of the centered body, which is typical of the β phase of this alloy [ 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, in producing new titanium alloys, the scientific community seeks to produce β-type alloys, as these materials tend to have a lower elastic modulus value than α-type alloys [ 28 ], which would increase the useful life of a biomedical implant, avoiding the failure effect known as “stress shielding.” Furthermore, α-type alloys have a higher atomic packing factor (compact hexagonal structure) than β-type alloys, which can result in a high hardness value due to the reduction in atomic interstices, making handling difficult for the forging parts, such as screws and plates orthopedic.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium alloys, such as Ti-6Al-4V ELI, Ti-13Nb-13Zr, and Ti-15Mo (in mass%), have been used as biomedical materials due to their proper mechanical properties, excellent corrosion resistance, and high biocompatibility with non-magnetic ( Kaur and Singh, 2019 ; Sarraf et al, 2022 ; Marin and Lanzutti, 2023 ; Pesode and Barve, 2023 ). Although titanium alloys are widely used in biomedical fields, they are expensive for refining, processing, and improving mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to biocompatibility and reaching the β-phase alloy for the new design of titanium-based alloys, it is important to keep in mind that pure Ti has a low wear resistance, which limits its usage in implants that come into contact with their own or neighboring bone. In fact, the wear behavior of Ti-based alloys is considered to be a crucial factor in their suitability for biomedical applications [26,27]. This is due to the fact that the generation of wear debris during the movement of artificial joints significantly contributes to the occurrence of aseptic loosening (mechanical loss results in the failure of the fixation of a prosthetic alloy component in the absence of infection) [28,29].…”
Section: Introductionmentioning
confidence: 99%